THE EFFECT OF THE PLAY AND COMMAND APPROACH TEACHING METHODS ON INCREASING VO2MAX OF STUDENTS AT STATE MIDDLE SCHOOL 15 PALU: PENGARUH METODE MENGAJAR PENDEKATAN BERMAIN DAN KOMANDO TERHADAP PENINGKATAN VO2MAX SISWA SMP NEGERI 15 PALU - Moh. Apriansyah Lurang; Andi Saparia; Nyoman Sukrawan; Didik Purwanto; Tri Murtono (Universitas Hamzanwadi, 2026)
Students’ low levels of physical fitness, particularly their vo₂max capacity, are a major problem in physical education classes. Monotonous instruction that fails to actively engage students is believed to be the primary cause. This study aims to determine the effect of the play-based and command-based teaching methods on improving students’ vo₂max, as well as to compare the effectiveness of these two methods. The study employed a quantitative approach using a two-group pretest-posttest experimental design. The sample consisted of 50 students divided into two groups, with 25 students each assigned to the play-based and command-based approaches. vo₂max was measured using the multistage fitness test (bleep test). Data analysis was performed using the Wilcoxon test, paired-sample t-test, independent-sample t-test, and Cohen’s d effect size. The results showed that the play-based approach had a significant effect on improving vo₂max with a significance value of 0.000 and an average increase of 2.092 mL/kg/minute, while the command-based approach showed no significant effect (p = 0.513). There was a significant difference in effect between the two methods, with the play-based approach being more effective (Cohen’s d = 4.174). In conclusion, the play-based approach is recommended as an effective Physical Education learning strategy to improve students’ physical fitness.